The Linkage between the Eastern Pacific Teleconnection Pattern and Convective Heating over the Tropical Western Pacific - Tan, Benkui; Yuan, Jiacan; Dai, Ying; Feldstein, Steven B.; Lee, Sukyoung (Journal of Climate, 2015)
The eastern Pacific (EP) pattern is a recently detected atmospheric teleconnection pattern that frequently occurs during late winter. Through analysis of daily ERA-Interim data and outgoing longwave radiation data for the period of 1979-2011, it is shown here that the formation of the EP is preceded by an anomalous tropical convection dipole, with one extremum located over the eastern Indian Ocean-Maritime Continent and the other over the central Pacific. This is followed by the excitation of two quasi-stationary Rossby wave trains. Departing from the subtropics, north of the region of anomalous convection, one Rossby wave train propagates eastward along the East Asian jet from southern China toward the eastern Pacific. The second wave train propagates northward from east of Japan toward eastern Siberia and then turns southeastward to the Gulf of Alaska. Both wave trains are associated with wave activity flux convergence where the EP pattern develops. The results from an examination of the E vector suggest that the EP undergoes further growth with the aid of positive feedback from high-frequency transient eddies. The frequency of occurrence of the dipole convection anomaly increases significantly from early to late winter, a finding that suggests that it is the seasonal change in the convection anomaly that accounts for the EP being more dominant in late winter. Chinese NSF [41130962, 41375060]; China Postdoctoral Science Foundation [2013M540014]; National Science Foundation [AGS-1139970, AGS-1036858, AGS-1401220]; National Oceanic and Atmospheric Administration Grant [NA14OAR4310190] SCI(E) EI ARTICLE bktan@pku.edu.cn 14 5783-5794 28